Analysis of marker substitutions in A/chicken/Astrakhan/2171-1/2020 H5N8 isolate of avian influenza virus recovered in the Astrakhan Oblast - N. G. Zinyakov; A. V. Andriyasov; Ye. V. Ovchinnikova; A. A. Kozlov; P. D. Zhestkov; D. B. Andreychuk; I. A. Chvala (Ветеринария сегодня)
At the end of 2020, a large-scale bird death was registered at one of the poultry farms in the Astrakhan region, the cause of which was avian influenza. Data on detection of the marker substitutions in viral proteins of avian influenza virus A/chicken/Astrakhan/2171-1/2020 isolate are presented in the paper. Type A Н5N8 avian influenza virus was identified with complex PCR-based methods in the submitted samples. Hemagglutinin gene fragment sequencing identified REKRRKR/ GLF, highly pathogenic avian influenza virus isolate-characteristic amino acid sequence of the hemagglutinin cleavage site. Phylogenetic analysis of nucleotide sequences of hemagglutinin gene segment (848–1105 bp ORF) allowed A/chicken/Astrakhan/2171-1/2020 H5N8 isolate to be classified to highly pathogenic avian influenza virus genetic clade 2.3.4.4. Comparative analysis of genome segments using available databases showed that A/chicken/Astrakhan/2171-1/2020 H5N8 virus related to А/Н5 avian influenza virus isolates detected in the Russian Federation in 2016–2020. Analysis of the studied virus isolate hemagglutinin amino acid identified AIV-characteristic G225QRG228 amino acids in the receptor-binding domain of the protein enabling high-affinity binding to avian epithelial cell SAα-2,3- gal receptors. Single mutations, 70G in NEP protein and 13Р in PB1 protein, out of the list of the reported influenza virus mutations affecting successful influenza virus replication in mammals were identified. No mutations affecting virus sensitivity to anti-viral medicines, rimantadin, amantadine, oseltamivir and zanamivir, were detected. The following mutations recognized as pathogenicity determinants in mice were found: 42S in the NS1 protein and 30D protein 215A in M1 protein.